Top Management Tools in Sales Managers’ Practice - Davidkov, Tzvetan; Yankulov, Yavor (Research Papers, 2021)
Research on the use of different management tools trace the evolution of leading trends in management. It outlines the content and limitations of the general management tools, as well as differentiating between them. The text introduces a clear-cut model of the top management tools and the results of a study among Bulgarian managers. There are two components to this research: to what extent are the subjects familiar with the tools listed; to what extent do they wish to learn more about them. Special attention is paid to the sales managers – which of the tools they are familiar with and which they use in their practice. A comparison is drawn between the sales managers and the production managers relative to the whole studied aggregate.